Artificial Intelligence Automatic Speech Recognition (ASR) untuk pencarian potongan ayat Al-Qu’ran - Salamun Salamun; sukri sukri; Khairul Amin; Luluk Elvitaria; Liza Trisnawati (Jurnal Komputer Terapan, 2022)
Indonesia is a country with the largest number of Muslims in the world, who read verses of the Qur'an often heard in various public places such as mosques, prayer rooms, and at various activities. Utilization of Automatic Speech Recognition (ASR) as word recognition which aims to find out the verses of the Qur'an that are read to increase knowledge about the verses and other supporting information as a means of preaching in conveying knowledge about the verses of Al-Qur'an. Al-Qur'an. Automatic Speech Recognitions (ASR) is designed using the Python programming language and uses the Django framework to display information about the verses that are read in the form of a web-based display. This research aims to create a technique and system for entering voice commands into machines, so that machines can understand what humans say and obey what they are told. This application converts data into text data using a voice recognition system automatically with a digital audio pattern of spoken words from a speech pattern computer model to produce the final output in the form of text that is stored in the database.